MOVEMENT PATTERN OF RUSUNAWA MARUNDA SHOCKING MARKET NORTH JAKARTA - Aisy, Karlina Rahadatul; Aflah, Saffanah Zhahirah; Azkiawati, Diana; Hantono, Dedi (Border: Jurnal Arsitektur, 2020)
The increasing needs of daily life is certainly involve the market. The market is one of place for business opportunities for traders, the majority of which have small businesses. As the number of consumer demand increases for the necessities of life, then formed a market known as the 'shocking market'. It named “shocking” market because the market is temporary with traders who are always moving locations to find a crowded point of buyers. The activity is only for some time and lasts only a few hours. Usually this shocking market stands at a place that has other functions, such as a sidewalk or open field that has a potential point of bustling buyers in the surrounding environment. The shocking market presence can be assessed through its movement patterns, in which the movement patterns of traders by means of groups and at certain times are the background of this study. The presence of the shock market was reviewed in order to uncover the pattern of movement of traders in the shock market in the Marunda Rusunawa area. The method used is a qualitative rationalistic method, with interview and observation techniques in the field. The results of this study shows the movement pattern of the shocking market traders in Marunda Rusunawa and the reasons behind them moving in groups.